Associations between prepregnancy body mass index, gestational weight gain and weight catch‐up in small‐for‐gestational‐age children - Lihua Huang; Shiwei Jiang; Jian Xu; Xiaoping Lei; Jun Zhang (Wiley, 2022)
Abstract Inadequate gestational weight gain (GWG) was related with a higher incidence of small‐for‐gestational‐age (SGA) births than appropriate GWG; however, the long‐term association of maternal GWG with weight catch‐up growth in SGA children remains unknown. The objective of this study is to evaluate the associations between prepregnancy body mass index (pBMI), GWG and weight catch‐up patterns in SGA children. Data were from the Collaborative Perinatal Project, an American multicentre prospective cohort study. A total of 56,990 gravidas were recruited at the first prenatal visit, and children were followed up until school age. Maternal pBMI, GWG and physical growth of the offspring at birth, 4 months, 1 year, 4 years and 7 years old were recorded. The latent class analysis was employed to form weight catch‐up growth patterns (appropriate, excessive, slow, regression and no catch‐up patterns) in SGA children. SGA children who developed the 'appropriate catch‐up growth' pattern and whose mothers had appropriate pBMI and GWG were chosen as the reference. Associations between GWG for different pBMI and weight catch‐up patterns were analysed by multivariate logistic regression models. A total of 1619 infants (9.45%) were born term SGA. After adjusting for relevant confounders, compared with SGA children whose mothers had appropriate pBMI and GWG, SGA children with maternal prepregnancy underweight (for inadequate GWG, GWG below recommendations, adjusted OR: 2.88, 95% CI: 1.13-7.31; for appropriate/excessive GWG, adjusted OR: 3.07, 95% CI: 1.74-5.42) or with prepregnancy normal weight but inadequate GWG (adjusted OR: 2.14, 95% CI: 1.36-3.38) were at a higher risk of having the 'no catch‐up growth' pattern. We suggest that SGA children with maternal prepregnancy underweight or inadequate GWG tend to have a poor weight catch‐up growth at least until school age.